Surface forces dominating tribological phenomena in nanoconfined liquids: A review - Chenyu Qiao; Yongxiang Sun; Yichun Han; Ziqian Zhao; Lifeng Ma; Hongbo Zeng (Friction)
Friction is ubiquitous and plays a key role in the functionality of many biological and engineering systems, from articular cartilage to machinery. While friction facilitates motion, it also causes wear and energy loss in moving parts. Lubricants (particularly liquid lubricants) are essential to reduce the negative effects of friction, and their properties (e.g., rheology and compatibility with friction materials) significantly influence lubrication performance and related mechanisms. The tribological phenomena between friction surfaces separated by a nanoconfined liquid film are governed by both external load and surface forces involved. Despite significant progress over the past few decades, the molecular and interfacial interaction mechanisms driving liquid-lubricated friction are not yet fully understood, and a comprehensive correlation between surface forces and tribological behaviors in nanoconfined liquids has not been fully established. In this review, we first summarize the latest understanding of fundamental concepts in surface forces, nano-rheology, and tribology in nanoconfined liquids. Representative tribological phenomena in nanoconfined liquids are analyzed and correlated with surface forces and liquid properties involved in specific cases. Additionally, advanced nanomechanical technologies (e.g., surface forces apparatus (SFA) and atomic force microscopy (AFM)), which show great potential in the field of tribology, are introduced. The advantages and current limitations of these technologies are also discussed. Moreover, key findings from recent tribological studies involving different liquids (both aqueous solutions and nonpolar liquids) are reviewed, and the underlying mechanisms of lubrication performance are analyzed from the perspective of surface forces. The future directions of tribology in nanoconfined liquids are discussed, providing insights and inspirations for developing effective lubrication strategies. This review enhances the understanding of nanotribology and correlates tribological phenomena with surface forces and rheology in nanoconfined liquids, offering new insights for developing advanced lubricants and wear-resistance materials.